General Practitioners as partners for a shared management of chronic HIV infection: an insight into the perspectives of Italian people living with HIV - Bruno, SR; Poliseno, M; Vichi, F; Esperti, S; Di Biagio, A; Berruti, M; Ferrara, S; Pisani, L; Saracino, A; Santantonio, TA; Lo Caputo, S (Public Library of Science, 2021)
Is it possible to achieve a collaboration between Infectious Diseases (ID) Specialists and General Practitioners (GPs) in the management of chronic HIV infection? A cross sectional survey was conducted among People Living with HIV (PLWHIV) attending the outpatient services of four Italian Infectious Diseases Centers to understand to which extent patients trust their GPs and involve them in the management of their chronic condition. Information about level of communication with GPs, subjective perception of the disease, and presence of co-medications were collected and matched with socio-demographic data using χ2statistics. A p<0.05 was considered statistically significant. From December 2019 to February 2020, 672 patients completed the survey, 59% males and 56% >50 years. Overall, 508 patients (76%) had informed GPs about HIV-positivity. Communication of diagnosis was significantly associated with age >50years, lower education level, history of disease >10 years and residency in Northern Italy. The "Undetectable = Untrasmittable" (U = U) concept was investigated as an indirect measure of perceived stigma. 23% of subjects was unaware of its meaning. Despite undetectable status, 50% of PLWHIV found difficult to communicate their condition to GPs, especially married (52% vs 48% of unmarried, p = 0.003), well-educated patients (51% vs 48, p = 0.007), living in Southern vs Northern Italy (52% vs 46%, p< 0.001). More than 75% of the participants consulted the ID specialist for co-medications and DDIs management, often complaining a lack of communication of the former with GPs. Overall, a good level of communication between PLWHIV and GPs was outlined, even if a wider involvement of the latter in HIV care is desirable.